2018
DOI: 10.1002/smll.201800901
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Modal NIR‐Fluorophore Conjugated Magnetic Nanoparticle for Imaging Amyloid‐β Species In Vivo

Abstract: Senile plaques, the extracellular deposit of amyloid-β (Aβ) peptides, are one of the neuropathological hallmarks found in Alzheimer's disease (AD) brain. The current method of brain imaging of amyloid plaques based on positron emission tomography (PET) is expensive and invasive with low spatial resolution. Thus, the development of sensitive and nonradiative amyloid-β (Aβ)-specific contrast agents is highly important and beneficial to achieve early AD detection, monitor the disease progression, and evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…However, fluoresce imaging is not quantitative, and the image information is a surface-weighted in vivo system. Thus, multimodal imaging utilizing a combination of MRI and fluorescent imaging could facilitate the creation of a novel imaging system [ 141 , 142 , 143 ].…”
Section: Optical Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fluoresce imaging is not quantitative, and the image information is a surface-weighted in vivo system. Thus, multimodal imaging utilizing a combination of MRI and fluorescent imaging could facilitate the creation of a novel imaging system [ 141 , 142 , 143 ].…”
Section: Optical Imagingmentioning
confidence: 99%
“…Hydrophobic iron oxide cores can be coated with silica shells using the reverse microemulsion method or siloxanes which contain hydrophobic parts, thus resulting in an MRI-detectable silica nanoparticle. Li et al reported Fe 3 O 4 @SiO 2 @SLCONHR nanoparticles by integrating highly Aβ-specific and turn-on fluorescence cyanine sensors for a neuroprotective dual-modal nanoprobe in vivo for both NIR imaging and MRI contrast [ 143 ]. Inorganic nanoparticles, such as Fe, are readily utilized as MRI biomedical imaging probes, due to their inherent T1- and T2-weighted contrasts.…”
Section: Optical Imagingmentioning
confidence: 99%
“…The NIRI was triggered only when the nanoassembly bound to Aβ due to the specificity of the fluorescence cyanine sensors for Aβ. Therefore, the colocalization of the NIRI and MRI signals provided a more accurate spatial distribution of Aβ in the AD brain (Y. Li, Xu, et al, 2018).…”
Section: Ad Diagnosis Using Functional Nanoassembliesmentioning
confidence: 99%
“…Additionally, a hydrophilic silica layer was reported to improve the dispersity and stability of Fe 3 O 4 NPs as well. [99] Apart from the commonly used contrast agents, cyanine has been conjugated with manganese oxide (MnO) nanoparticles which remain in a relatively early stage. For example, Ye's lab modified MnO NPs with N-(Trimethoxysilylpropyl)ethylene diamine triacetic acid, trisodium salt to confer water dispersibility and stability; PEG-Cy5.5 was then conjugated on the surface (65) for dual-modal imaging of brain gliomas (Figure 12c).…”
Section: Mri/nirfmentioning
confidence: 99%